Research of mission success importance for a multi-state repairable k-out-of-n system. (February 2018) - Zhao, Jiang-Bin; Hou, Pei-Yong; Cai, Zhi-Qiang; Li, Yang; Guo, Peng
For the reliability analysis of complex equipment system, one of the key objectives is that the equipment can complete the specified mission as expected. First of all, this article presents the analysis method of mission success importance for a multi-state k -out-of- n repairable system based on multi-state multi-valued decision diagram as well as the implementation procedure. Second, the engineering significance of mission success importance for a multi-state repairable 2-out-of-3 system is discussed by comparing the component order of mission success importance with multi-state Birnbaum importance, multi-state Fussell–Vesely importance, performance achievement worth, and performance reduction worth. Finally, the change rule of mission success importance is presented for a multi-state 2-out-of-3 repairable system when the reliability of a component is changed. The analysis results show that the engineering significance and change rule of mission success importance could provide effective support for mission success optimization of a repairable system.